Comprehensive Handbook of Psychological Assessment : Volume 2 personality assessment - Hersen, Michel; Hilsenroth, Mark J.; Segal, Daniel L. (Hoboken, N.J. : John Wiley & Sons, 2004)
Clinicians and researchers who use these instruments will find this volume invaluable, as it contains the most comprehensive and up-to-date information available on this important aspect of practice.
v. 1. Intellectual and neuropsychological assessment / editors, Gerald Goldstein, Sue R. Beers -- v. 2. Personality assessment / editors, Mark J. Hilsenroth, Daniel L. Segal -- v. 3. Behavioral assessment / editors, Stephen N. Haynes, Elaine M. Heiby -- v. 4. Industrial and organizational assessment / editor, Jay C. Thomas.
Includes bibliographical references and indexes.
Keywords: Psychological tests